Overexpression of a “Candidatus Liberibacter Asiaticus” Effector Gene CaLasSDE115 Contributes to Early Colonization in Citrus sinensis - Du, Meixia; Wang, Shuai; Dong, Liting; Qu, Rongrong; Zheng, Lin; He, Yongrui; Chen, Shanchun; Zou, Xiuping (Frontiers in Microbiology, 2022)
Huanglongbing (HLB), caused by 'Candidatus liberibacter asiaticus' (CaLas), is one of the most devastating diseases in citrus but its pathogenesis remains poorly understood. Here, we reported the role of the CaLasSDE115 (CLIBASIA_05115) effector, encoded by CaLas, during pathogen-host interactions. Bioinformatics analyses showed that CaLasSDE115 was 100% conserved in all reported CaLas strains but had sequence differences compared with orthologs from other 'Candidatus liberibacter'. Prediction of protein structures suggested that the crystal structure of CaLasSDE115 was very close to that of the invasion-related protein B (IalB), a virulence factor from Bartonella henselae. Alkaline phosphatase (PhoA) assay in E. coli further confirmed that CaLasSDE115 was a Sec-dependent secretory protein while subcellular localization analyses in tobacco showed that the mature protein of SDE115 (mSDE115), without its putative Sec-dependent signal peptide, was distributed in the cytoplasm and the nucleus. Expression levels of CaLasSDE115 in CaLas-infected Asian citrus psyllid (ACP) were much higher (~45-fold) than those in CaLas-infected Wanjincheng oranges, with the expression in symptomatic leaves being significantly higher than that in asymptomatic ones. Additionally, the overexpression of mSDE115 favored CaLas proliferation during the early stages (two months) of infection while promoting symptoms development. Hormone content and gene expression analysis of transgenic plants also suggested that overexpressing mSDE115 modulated the transcriptional regulation of genes involved in systemic acquired resistance (SAR) response. Overall, our data indicated that CaLasSDE115 effector contributed the early colonization of citrus by the pathogen and worsened the occurrence of Huanglongbing symptoms, thereby providing a theoretical basis for further exploring the pathogenic mechanisms of Huanglongbing disease in citrus.